Effect of Regional Intravenous Limb Perfusate Volume on Synovial Fluid Concentration of Amikacin and Local Venous Blood Pressure in the Horse. Issue 7 (11th August 2016) - Moser, Darla K.; Schoonover, Mike J.; Holbrook, Todd C.; Payton, Mark E.
Abstract : Objective: To determine the effect of volume of amikacin perfusate for intravenous regional limb perfusion (IVRLP) via the cephalic vein in standing, sedated horses on (1) amikacin concentrations in the synovial fluid of the radiocarpal joint (RCJ) and distal interphalangeal joint (DIPJ) and, (2) amikacin concentration in the systemic circulation, and (3) regional intravenous pressure. Study Design: Randomized cross‐over design. Animals: Six adult horses. Methods: Each horse received IVRLP using 4 perfusate volumes (10, 30, 60 & 120 ml) in random order, after a minimum of 1 week washout. After application of a pneumatic tourniquet, IVRLP with 1 g of amikacin in 0.9% NaCl was performed. Synovial fluid from the RCJ and DIPJ, and systemic and regional venous blood were sampled, and regional blood pressure was measured, immediately before perfusion (time 0), and 15 and 30 minutes after perfusion but before tourniquet release. Results: No difference was observed in the mean amikacin concentration of synovial fluid for the 4 perfusate volumes ( P >.09). For all volumes, mean amikacin concentration for DIPJ synovial fluid was higher than for RCJ ( P <.0001). The mean amikacin concentration in DIPJ synovial fluid was therapeutic for resistant pathogens using the 10, 60, and 120 mL volumes but the mean amikacin concentration for RCJ synovial fluid was not therapeutic for resistant pathogens with any perfusate volume. All volumes resulted in an immediate increase in mean regional intravascular pressure after perfusion ( P <.0001) but was not different across the 4 perfusate volumes. Conclusion: Cephalic IVRLP of 1 g of amikacin diluted to a volume of 10–120 mL with 0.9% NaCl will achieve amikacin concentrations therapeutic for resistant pathogens in the synovial fluid from the DIPJ. Concentrations below therapeutic levels for resistant pathogens are reached in the synovial fluid from the RCJ.